The Capability Analysis of High Order Thinking Skills (HOTS) on Dynamic Electricity Material in Junior High School - Ani Rahmawati; Nur Lailatin Nisfah; Sentot Kusairi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
The study aims to determine student’s High Order Thinking Skills (HOTS) and to find out the causes of student’s HOTS on dynamic electricity material. The number of samples involved 59 students consisting of 30 students from the excellence class and 29 students from the regular class. The research instrument used consisted of 8 Multiple Choice Questions (MCQs). Questions have been validated, and reliability has been tested in the medium category (Alpha Cronbachs: 0.44). The data analyzed using descriptive analysis. The average student’s HOTS is 59.98% indicating the medium category. The results of the student’s HOTS on the analysis provided by students from excellence classes are 71.25% indicating high category and regular class 48.71% indicating medium category. The results of the analysis show that student’s HOTS is on medium category because students having difficulty in making connection one concept to another concept and using mathematics as a tool in solving physics problems. The results as a reference for improving student’s HOTS. This research can be developed by increasing the sample and expanding the material being tested.